Mutual Interaction Effect Analysis of Workers Six-Distinctive Factors of Safe Weight Model - O.A. Muyiwa; Olusegun Gabriel Akanbi (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Introduction: An ergonomic mathematical model to compute safe weight lift was formed with the principle of strain energy to limit the risk of low back pain among construction employees in Nigeria. However, the mutual interaction effect of the selected factors has not yet been studied.Objective: To analyze the mutual interaction effect of compounded chosen factors including biomechanical factors (body weight, spinal shrinkage, spine length), physiological factors (age, gender), and psychophysical factors (surrounding temperature, lift frequency).Method: The data were collected using ZT-160 scale, tailor tape rule, fly-back timing, and RH/Temperature pen from fifty male manual construction workers selected using purposive sampling technique. The data were analyzed using Ms Excel and SPSS with multiple linear regression, regression curve estimate, and analysis of variance at an alpha level of 0.05.Result: The multiple linear regression investigation showed that the mutual interactions of the compounded masculine workers' factors were significant (p=0.00) and gave R²=0.94. The regression curve estimate predicted the existence of a quadratic relationship with the safe weight lift (p=0.00), and analysis of variance revealed that the selected factors were significant (p=0.00) with F-test=404.53.Conclusion: The mutual interactions of the selected factors were significant. Hence, it can be used for decision-making for the safety management of male laborers involved in load handling.